(untitled) (Development Service Industry Management, 2025)
The article examines the global experience of creating hydrogen clusters and substantiates their role in decarbonising the metallurgical industry of Ukraine. The article analyses foreign practices of introducing hydrogen technologies into heavy industry on the example of Germany, France, the Netherlands, the USA, Japan and Australia, and identifies key approaches to their adaptation to national conditions. The main advantages of the cluster approach are identified, including optimisation of hydrogen transportation costs, reduction of CO₂ emissions, integration of renewable energy sources and increase of competitiveness of metallurgical enterprises. The economic and technical prerequisites for the creation of a hydrogen cluster based on Metinvest Group’s assets are assessed, and the prospects for attracting international investment and cooperation with foreign partners are considered. A model for the integration of hydrogen technologies into the Ukrainian metallurgical complex is proposed, which includes the modernisation of production facilities, the creation of a hydrogen logistics network and the development of research centres to develop innovative solutions. The key challenges to the implementation of hydrogen clusters are identified, including the high cost of initial investment, the need to create appropriate infrastructure and the need for government support. The article substantiates strategic directions for the development of the hydrogen economy in Ukraine, including a state incentive policy, integration of research institutions into the clustering process, and attraction of foreign investors. The results show the prospects of hydrogen technologies for improving the environmental efficiency of Ukrainian metallurgy and its integration into the global low-carbon steel market. The proposed recommendations can be used to develop a national strategy for the hydrogen industry and adapt international best practices to Ukrainian realities.